Circuit Design for Thermal Compensation of Avalanche Photodiode - Chughtai, M. T. (Engineering, Technology & Applied Science Research, 2019)
It has been observed that the breakdown voltage of the avalanche photodiode (APD) changes with the change in the ambient temperature. This situation may result in a poorer signal to noise ratio and sometimes to permanent damage to the APD. In order to overcome these problems, various considerations may be taken into account, including maintaining the temperature of the APD permanently or the design of a bias system, which would be self-adjusting according to any changes in the temperature. The latter technique was adopted and the design of a bias supply is presented in this article.